FOOD ANALYSIS OF BOXING DIET PRODUCTS FOR CHILDREN - Otajonov I.O; Ochilov T.J; Karaeva M.M (Western European Studies, 2025)
Of particular importance for students-athletes who strive to achieve high results are the issues of rational nutrition, for this purpose, the article examined the seven-day diet of student-athletes involved in the sport of boxing in an accounting method and analyzed the amount of food in it. In conclusion, athletes who are engaged in boxing sports, the diet of food is almost consistent with the norms recommended by experts, but when drawing up a diet, it is necessary to draw up and control the diet individually, taking into account the weight of athletes and the tasks set for them
Keywords: boxing; athletes; diet